A Study on Nutritional Status Among Regular Gym Goers in and Around Chennai, India - Thirumurugan, Ettiyappan; Venkatesan, Kalpana Devi; Tamilmani, Pavithra; Preetha, Devika; Selvanathan, Joyce Albert Princy Mariya; Mohandas, Dhanyasree; Sathik, Ameer Basha; Manjunathan, Santhosh Kumar; Sheeba, Ashika Kannadhas (Makara Journal of Health Research, 2025)
Background: The increasing sales of sports supplements indicate a concerning trend, as many gym-goers may misuse these products owing to misinformation and insufficient knowledge, potentially impacting their performance. This issue is further compounded by specific gym trainers who may lack comprehensive information and inadvertently influence their clients' choices. To address this concern, the present study evaluated dietary supplement practices and sports nutrition knowledge among regular gym-goers at fitness centers in Chennai, India. Methods: A cross-sectional survey was conducted from November 2023 to May 2024 using a validated questionnaire distributed across Chennai, India. A total of 450 participants were included in the final analysis, consisting of individuals aged 20–50 years. Results: Among the respondents, the primary professionals endorsing dietary supplement use were gym trainers (22.6%), followed by nutritionists (13.1%) and medical doctors (3.9%). Notably, nearly one-third of the respondents reported acquiring these supplements from specialized sports nutrition stores (23.5%), pharmacies (7.8%), and online platforms (27.1%). Conclusions: The findings indicate that 61% of respondents demonstrated sufficient nutritional knowledge and skills, while the remaining showed inadequate knowledge. Overall, this study underscores the urgent need to educate the public regarding the prudent use of dietary supplements and to implement regulations requiring similar educational initiatives for trainers.